Analisis Semiotik Charles Sanders Pierce pada Novel “Garis Waktu” Karya Fiersa Besari - Pratiwi, Sekar; Yanti, Prima Gusti (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
This study focuses on the analysis of semiotic signs in Fiersa Besari's novel Garis Waktu using Charles Sanders Peirce's semiotic theory to explore the meaning and symbolism in the narrative. Although previous studies have analyzed this novel in terms of language style and morphology, not many have studied the application of Peirce's semiotic theory in depth, especially in the trichotomy relationship between icons, indexes, and symbols. This study aims to fill this gap by applying a descriptive qualitative approach. Data were collected through listening and note-taking techniques from relevant quotations in the novel, then analyzed using a manual coding method based on Peirce's theory. The main findings show that symbolism such as